2016
DOI: 10.1037/rep0000089
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Social Provisions Scale in people with multiple sclerosis.

Abstract: Objective This study examined the factorial and construct validity of the Social Provisions Scale (SPS) in a sample of people with multiple sclerosis (MS). Method Participants included 292 individuals with MS (83.9% women) recruited from the Greater Illinois, Gateway, and Indiana chapters of the National Multiple Sclerosis Society. Participants completed the SPS and pain, fatigue, depression, anxiety, MS self-efficacy, quality of life and satisfaction with life measures. Factorial validity was tested using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
31
2
9

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(44 citation statements)
references
References 66 publications
2
31
2
9
Order By: Relevance
“…The amount of variance of each first order factor that is accounted for by a second-order factor differs substantially in our samples compared to others. Second-order factor loadings of the original scale reported by Chui and colleagues [31] ranged from λ = .65-.90, whereas in the current investigation factor loadings for the weight management specific scale ranged from λ = .57-.97.…”
Section: Mancini and Bliesznercontrasting
confidence: 59%
See 1 more Smart Citation
“…The amount of variance of each first order factor that is accounted for by a second-order factor differs substantially in our samples compared to others. Second-order factor loadings of the original scale reported by Chui and colleagues [31] ranged from λ = .65-.90, whereas in the current investigation factor loadings for the weight management specific scale ranged from λ = .57-.97.…”
Section: Mancini and Bliesznercontrasting
confidence: 59%
“…In contrast, Chiu, Motl, & Ditchman [31] found close fit of their data to the hierarchical model in a sample of 292 individuals with multiple sclerosis (MS). Extreme inter-factor correlations and multicollinearity previously reported for the original scale [13][14][15] were not observed in this sample.…”
Section: Mancini and Bliesznermentioning
confidence: 94%
“…The second part of the common section included questions about concerns, behaviours and habits, need for information, and work modality changes due to COVID‐19; the Patient Health Questionnaire 2 (PHQ‐2) [10] the Perceived Stress Scale (PSS) [11] and the Social Provision Scale 10 items (SPS‐10) [12]. …”
Section: Methodsmentioning
confidence: 99%
“…Moran et al ( 2019 ) found that the parents living in the disadvantaged circumstance of a refugee center in Ireland relied heavily on local services for emotional and financial support to cope with their living conditions. The availability of different types of social support might increase caregivers’ self-esteem and self-efficacy, which could be regarded as a critical component for living a positive, healthy, and productive life (Chung-Yi et al, 2016 ).…”
Section: Caregiver Social Support Caregiver Depression and Children’s Behavioral Healthmentioning
confidence: 99%